“REGULATORY CHILL” IN ISDS - Axtamova Yulduz Axtamovna (Web of Journals Publishing, 2024)
The article involves a dispute arising out of circumstances, where the investor seeks damages from the host state for having revoked a permit in response to protests by a local population against the investment operations. This article analyzes how the arbitral award of the Beer Creek Mining case has contributed to the “regulatory chill”. Arbitral awards of ISDS cases have greatly contributed to the emergence of the “regulatory chill” through broad and investor-protection-oriented interpretation of investment treaty provisions. Therefore, it is essential to examine cases concerning the public-interest actions of the states, which shed light on the lessons to be learnt for drafting “balancing provisions”. One of these cases is Beer Creek Mining v. Peru.
Keywords: IIAs, arbitral awards, legitimacy of International investment law.